A contribution to encourage the dissemination of academic publishing: Finding diffusion media by means of a search engine based on semantic technologies - Piedra Pullaguari, N. (2016)
Scientific production reflects the advances of an academic or research activity; also, it reflects the efforts and issues in which people are engage. The researcher's contributions in each field of knowledge should be highlight in order to foster a systematic improvement of research and achieve recognition of researchers. In the current educational context, the role of creating knowledge is not exclusive to teachers, students are also encouraged to participate and even to lead academic and research projects. This fact, coupled with the need for universities achieve to become research entities, it increase the need for finding events or journals in order to disseminate the researches results. Therefore, specialized search tools are required for users to reach better results. With the aim of helping the academic staff to find the most appropriate media to publish his/her scientific production, in this paper, the authors present a technological platform that consolidates data from different sources as catalogs of call for papers and scientific databases. Later on, each diffusion media is enriched with open data available in the Web; this process leverages relationships established between semantic resources available in repositories created collectively. The semantic enrichment of the media has allowed implement an improved search service, which attempts to overcome the limitations of traditional engines based on matching keywords. © 2016 IEEE.